L’ENCADREMENT PHILOSOPHIQUE ET CULTUREL DE L’ACTE CRÉATEUR DANS LA LITTÉRATURE ET LA MUSIQUE - BENCE-MUK, Mirona (Studia Universitatis Babes-Bolyai Musica, 2015)
The present article opens the philosophical and aesthetical horizon that anticipates the musical horizon and marks at the same time, at the theoretical level, the passage from aesthetics to poetics, respectively to the semantic and metaphorical categories, as initially proposed by L. Blaga and re-evaluated by E. Coşeriu. Blaga’s theory of metaphor is grounded, of course, on his philosophical conception about “the horizon” of human existence and consciousness, but also on the theses concerning a certain “spatial horizon of unconscious”, especially when referring to that kind of act of creation that is oriented toward mystery and for revelation. To this level of unconscious the philosopher also relates a new metaphorical category, which can be found at the phonological and metrical level within the word, respectively within poetry, and which he calls “acoustic metaphor”. The acoustic of the word constitutes, in fact, the basic feature that relates text to music and it is the first level which is intuitively exploited by the art-making subject. In order to exemplify the way of functioning of the “acoustic metaphorism” within the complex and deep process of sense articulation at textual level, we sketch below a complementary account to the theoretical framework presented here and refer to the exploitation of the same “expressive” (or metaphorical) dimension by the great linguist Sextil Puşcariu. More precisely, we correlate the linguist’s analysis on Mihai Eminescu’s poem Rugăciune with the analysis of one of the most recent Romanian choral composition, which uses the verses of the same poetic text.